2001
DOI: 10.1037/1064-1297.9.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic morphine treatment on responding for intracranial stimulation in female versus male rats.

Abstract: Morphine was administered to Sprague-Dawley rats twice daily at 0, 3, 10, and 20 mg/kg/ injection during Weeks 1, 2, 3, and 4, respectively; responding for medial forebrain bundle stimulation was assessed 1, 2, and 3 hr after morning injections in female versus male rats. There were no sex differences in responding under control conditions (Week 1). Morphine's effect on response rate depended on dose, time post-injection, stimulation frequency, and day of treatment. Significant sex differences in morphine's ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
3
4
1
Order By: Relevance
“…However, as early as the third day of treatment, doses of 5 and 10 mg/kg morphine ceased to produce rate-decreasing effects, and rate-increasing effects occurred with an earlier onset and similar duration of action. The present results also agree with studies using more sophisticated procedures that showed reductions in initial rate-decreasing effects and/or increased expression of rate-increasing effects during repeated morphine treatment (Carlezon and Wise, 1993; Easterling and Holtzman, 1997; Craft et al, 2001). The present study adds to this literature by evaluating effects of a broad range of morphine doses on responding maintained across a broad range of ICSS rates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, as early as the third day of treatment, doses of 5 and 10 mg/kg morphine ceased to produce rate-decreasing effects, and rate-increasing effects occurred with an earlier onset and similar duration of action. The present results also agree with studies using more sophisticated procedures that showed reductions in initial rate-decreasing effects and/or increased expression of rate-increasing effects during repeated morphine treatment (Carlezon and Wise, 1993; Easterling and Holtzman, 1997; Craft et al, 2001). The present study adds to this literature by evaluating effects of a broad range of morphine doses on responding maintained across a broad range of ICSS rates.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with this sensitivity, some studies reported rapid facilitation of ICSS after acute treatment with low mu agonist doses (Kornetsky and Esposito, 1979; Carlezon and Wise, 1993; Jha et al, 2004), although this finding has not always been obtained (Stratmann and Craft, 1997; Pereira Do Carmo et al, 2009b). Other studies have provided evidence to suggest that, in accordance with earlier studies using simpler procedures, facilitation of ICSS may be more robust later in the time course after acute mu agonist treatment or after chronic treatment (Carlezon and Wise, 1993; Craft et al, 2001; O'Neill and Todtenkopf, 2010). The main goal of this study was to further evaluate the role of dose, pretreatment time and regimen of repeated treatment as determinants of morphine effects on ICSS using a “frequency-rate” procedure, in which the frequency of the reinforcing electrical stimulus was varied to generate a wide range of response rates during each daily session.…”
Section: Introductionsupporting
confidence: 68%
“…Acute administration of the mu opioid agonist morphine did not facilitate ICSS in a discrete-trial procedure in either male or female rats (Stratmann and Craft, 1997), but a subsequent study using a hybrid frequency-rate procedure did show sex-dependent effects (Craft et al, 2001). Specifically, this study found that morphine was more potent to depress ICSS in males and more potent to facilitate ICSS in females.…”
Section: A Statesmentioning
confidence: 63%
“…For example, nearly all ICSS studies have been conducted in male subjects, but the few studies that have been conducted with females have identified intriguing sex differences in effects of some drugs such as opioids (Craft et al, 2001;Russell et al, 2013). Systematic examination of state/trait variables on drug effects in ICSS procedures may help to identify conditions under which selected drugs are most likely to produce an abuse-related effect.…”
Section: B Opportunities For Future Researchmentioning
confidence: 99%
“…Nonetheless, the present evidence for greater sensitivity of females to ICSS depression by flibanserin is not likely to reflect a generally heightened sensitivity of females to treatments that depress ICSS. For example, the kappa opioid receptor agonist U50488 was more potent to depress ICSS in males [35] and morphine also decreased rates of responding to a greater degree in males [58]. Consequently, the reliability and underlying mechanisms of sex differences in flibanserin effects on ICSS or other behaviors may warrant further study.…”
Section: Discussionmentioning
confidence: 99%